Pengembangan Perintah Gestur Tangan Menggunakan Leap Motion untuk Aplikasi Floorplanner - Marcellino, Hendy; Ario Yudo Husodo; Fitri Bimantoro (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Architecture is part of the art of life and works best when it seems to give expression to the life that inhabits it. As technology has developed a lot, the field of architecture has also experienced many developments supported by technology such as making architectural designs. The development experienced in making architectural designs is that it is no longer required to draw design choices with side views on a lot of paper but instead use a simulation application for making architectural designs that are displayed through a monitor layer in 3D so that they can see more realistically. After many innovations emerged regarding simulation applications which generally still use hardware such as a mouse, then these innovations shifted to connecting the simulation application with the virtual world where hardware such as a mouse has been replaced by using gestures or limb movements such as parts of the hand or other parts of the body. While other fields like medic already use virtual tool interaction, architecture fields still just use mouse and keyboard. One of the virtual interaction devices used to be able to detect fingers and palms to interact with 3D simulation applications is Leap Motion. Leap Motion is starting to be widely used to carry out various ways of interacting with hands because it is more interactive and interesting to use even many people think that it can be used for hand rehabilitation or therapy too. However, even though many innovations have developed, there is still no innovation in the use of a hand gesture command system using Leap Motion for simulation applications to design architectural designs in 3D views. Based on these things, the authors designed and developed hand gesture commands using Leap Motion for Architectural Design App. The hand gesture command system used for the Floorplanner simulation application will be tested using a system usability scale by users with architectural, informatics, and unfamiliar backgrounds. Based on the tests carried out, it can be seen that the system is running properly even though it requires getting used to the device first and getting a score from the System Usability Scale of 59,167 out of scale from 0 to 100 which means it is still accepted by users or declared as "Marginally Acceptable" category.